2021
DOI: 10.3390/ijms22041708
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology and Application of Aloe vera-Based Scaffolds in Tissue Engineering

Abstract: Aloe vera (AV), a succulent plant belonging to the Liliaceae family, has been widely used for biomedical and pharmaceutical application. Its popularity stems from several of its bioactive components that have anti-oxidant, anti-microbial, anti-inflammatory and even immunomodulatory effects. Given such unique multi-modal biological impact, AV has been considered as a biomaterial for regenerative medicine and tissue engineering applications, where tissue repair and neo-angiogenesis are vital. This review outline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 102 publications
(184 reference statements)
0
14
0
Order By: Relevance
“…In this study, the culture supernatant of the Bifidobacterium b. showed the potential to increase angiogenesis in the experimental groups. Hence, a comparison of the experimental group 1 and the sham group showed that despite the common hydrogel composition in both dressings and the antibacterial and antiviral properties of the constituents of hydrogels (23,24) in preventing microbial growth and reducing inflammation and pain (8,25), the experimental group 1 has a better performance in the process of wound healing and angiogenesis because of the probiotic agent.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the culture supernatant of the Bifidobacterium b. showed the potential to increase angiogenesis in the experimental groups. Hence, a comparison of the experimental group 1 and the sham group showed that despite the common hydrogel composition in both dressings and the antibacterial and antiviral properties of the constituents of hydrogels (23,24) in preventing microbial growth and reducing inflammation and pain (8,25), the experimental group 1 has a better performance in the process of wound healing and angiogenesis because of the probiotic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing AVE as an additive at the optimum dose stimulates lipase, amylase, and trypsin excretion of the fish gut, so it doesn't use the amino acids as an energy source and is directed to muscle-building (Gabriel et al, 2017). A. vera is a good source of thiamine, riboflavin, folic acid, and essential and non-essential amino acids (Ahlawat and Khatkar, 2011;Darzi et al, 2021). Also, polysaccharides are the major component of A. vera and have been reported to stimulate erythropoiesis (Ni et al, 2004), which can boost the gut microbial community and also improve feed digestibility and availability of nutrients from feedstuffs, and shorten the feed transit time hence there is a beneficial effect on digestive enzymes (Citarasu, 2010;Yu et al, 2018).…”
Section: % (Cfe) [I and J]mentioning
confidence: 99%
“…However, this method still suffers from off-target toxic effects on normal tissue. This increases the need to focus on localized delivery of cytotoxic anticancer agents [106]. Implementation of a biocompatible system after tumour surgery can get rid of remaining residuals and control tumour relapse.…”
Section: Anticancer Nanofibersmentioning
confidence: 99%
“…Implementation of a biocompatible system after tumour surgery can get rid of remaining residuals and control tumour relapse. Nanofiber loaded with anticancer agents can act as a novel effective delivery system for such use due to its large surface area, porosity, and tensile flexibility [48,49,106].…”
Section: Anticancer Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation